Understanding the Well-Being of Recent College Graduates: Income is not Enough. Issue 1 (2nd January 2020) - Senter, Mary Scheuer; Spalter-Roth, Roberta
ABSTRACT: Given difficult economic times experienced during the Great Recession and the years following, coupled with the rising cost of higher education, there is increasing pressure by federal and state governments, accreditors, college administrators, parents, and students to view alumni salaries as the key outcome of a baccalaureate degree. Supporters of a liberal education have decried the growth of the individualistic orientation of those who insist that the main purpose of a college education is to secure a high-paying job rather than personal well-being and civic participation. This article, focuses on a series of measures of college outcomes that are proxy measures for a "great job" and a "great life, " using data from a longitudinal study of sociology majors from the class of 2012. For the relatively small number of respondents answering the third wave of the survey, being a sociology major seems to have positive implications for early post-baccalaureate life. Further, respondents who find that sociological concepts and skills learned as undergraduate majors help on the job are often more likely than others to experience positive outcomes. In general, income from jobs is not the sole predictor in most of the multivariate models, although the sample of respondents may be biased toward those who care less about income.